The wise provisioning of social media among the young people of Tanjung anom Village, Deli Serdang - Masril, Munzaimah; Sabarina Sitepu , Yovita (Talenta Publisher, 2019)
The intensity of social media consumption for young people is now very high, due to the rapid flow of information circulating directly proportional with to the ease of access the social media itself. But there are still some young people who have not equipped themselves with the ability to recognize the benefits and also the dangers of social media consumption itself. The results of observations through the community partner show that the young people in Tanjung Anom district tend to assume information obtained through social media is information from trusted sources. The lack ability of the young people to recognize the benefits and impacts of social media consumption is due to the fact that they rarely get socialization or education about the impact of social media consumption from the government or non-government organizations that may concern about it. This phenomenon certainly needs attention because the information flow circulates very quickly and easily through the various social media platform, it would be very dangerous if these young people then become one of the parties who carry on the information obtained without filtering first. These community service activities carried out at the young people community in Tanjung Anom district discussing about the social media platforms, the ethics in social media consumption, and also sharing about various problems may occur when accessing information on social media. This activity is expected to initiate small changes related to the ability of social media literacy for young people in the Tanjung Anom district.